Truth and Law in Post-Communist Society. Notes on the Margins of Tadeusz Buksiński’s Book Prawdy w polityce [Truths in Politics] - Raburski, Tomasz (Sensus Historiae, 2022)
The paper examines the postwar history of the principle of material truth in Polish law, as well as its philosophical foundations. Tadeusz Buksiński’s book Prawdy w polityce (2018) serves as the starting point for exploring the Marxist concept of truth. The article further describes how this concept was reflected in socialist positivism. Subsequently, the article discusses how the Marxist interpretation of the material truth principle eroded, but the letter of law remained unchanged. A moral discourse of political opposition emerged, in which truth played an important role. In consequence, despite the dramatic transformation of the substance of the material truth principle (from Marxist to classical conceptions of truth), its institutional form has remained unaltered.